مستوى الشعور بالأمن النفسي لدى عينة من طلبة كلية الآداب بجامعة بني وليد ) (Comprehensive Journal of Science, 2025)
This study aimed to identify the level of psychological security among a sample of students from the Faculty of Arts at Bani Walid University. For this purpose, the researcher used the descriptive method. The sample was selected randomly, and its number reached (50) students from the Faculty of Arts. In order to achieve the study objective, the Psychological Security Scale, prepared by Maslow, was used. It included (75) items requiring responses of (Yes), (Not Sure), (No). The scale was translated into Arabic by (Dawani) and (Dirani) in (1).Face validity was established by presenting it to a group of expert reviewers from the faculty of psychology, numbering (9) reviewers. They expressed their opinions on the clarity, comprehensiveness, and suitability of the scale items, and in terms of their ability to measure the study. The reviewers found the scale items to be clear and representative, and thus the scale achieved face validity. Its reliability was established byThe half-tested sample of (30) students from the Faculty of Arts at Bani Walid University had a reliability ratio of (85%). This indicates that the reliability coefficient of the scalehas an excellent effect. Thus, we find that the scale has excellent indicators of validity and reliability and is suitable for application to the target study sample. The results obtained by the researcher showed that the sample members recorded high levels of psychological security, ranging from 0% to 90%, while they recorded moderate levels ranging from 62% to 70%. The sample members also obtained low levels of psychological security, ranging from 46% to 9636.psychological security among the students. It also appeared that the sample members recorded very low levels of psychological security, ranging from 10% to 20. Based on the study results, the researcher made a number of recommendations and suggestions.
Keywords: الامن النفسي و طلبة الجامعة